The effect of input parameters on visco-elastic odels of crustal deformation - Lorenzo-martín, F.; Wang, R.; Roth, F. (Física de la Tierra, 2002)
The increasing quality of data on time-dependent deformation of the Earth’s surface can be used to extract more details on the spatial and temporal development of earthquake-related crustal deformation. Different variables are involved in these processes, some of them more accurately determined than others. We modelled surface deformation on a subduction zone, in a medium composed of an elastic layer over an inelastic half-space. We analyse the effect that three of the less accurately determined variables (viscosity of the half-space, thickness of the elastic layer and dip angle of the fault plane) have on the displacement field. We show that the variation of model parameters leads to a stable variability distribution in the deformation fields. We show which is the most appropriate data to be used to derive values for the studied parameters. The best data to derive the value of the viscosity is the post-seismic deformation over the area where the rupture takes place, although any area with large magnitude post-seismic displacements can provide profitable data. For the thickness of the elastic layer it is also advisable to use post-seismic data from the area above the fault plane, whereas the dip is better determined by means of co-seismic data.